Differentiated Mathematics Instruction in Jamaica: Educator Perspectives on Diverse Learning Needs - Jani, Mahesh (Journal of Educational Research and Policies, 2026)
This study explores teachers' use of differentiated instruction to improve mathematics performance among struggling learners and students with exceptionalities in Jamaica. Eight teachers from seven schools participated in this phenomenological research. Findings highlight the benefits of differentiated instruction despite challenges such as large class sizes, limited resources, and teacher workloads. Recommendations include specialized training and resource allocation to enhance instructional effectiveness.